Good agricultural practices, farm performance, and input usage by smallholders: Empirical evidence from Nepal. Issue 3 (5th November 2018) - Bairagi, Subir; Mishra, Ashok K.; Giri, Anil
Abstract: This study examines the impact of good agricultural practices (GAP) on the farm income and fertilizer usage of smallholders in Nepal. Using qualitative variables, we first construct a GAP‐index, a measure of the intensity of GAP adoption. The findings show that a GAP‐index constructed through principal component analysis performs better than a GAP‐index constructed with Markowitz's portfolio method. Results reveal a positive and significant relationship between the GAP‐index and farm income and a negative and significant relationship between the GAP‐index and fertilizer usage. Public and private partnerships that incentivize the adoption of GAP can help increase the income of and reduce fertilizer usage by smallholders.